Efficient method for synthesis of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural and fructose using Pd/CC catalyst under aqueous conditions - Rathod, Pramod V.; Jadhav, Vrushali H. (ACS Sustainable Chemistry & Engineering, 2018)
Pd/CC catalyst was synthesized from readily available biomass-derived D-glucose. The catalyst was characterized using various techniques such as Fourier transform infrared spectroscopy, powder X-ray diffraction, energy dispersive X-ray analysis, scanning electron microscopy, C-13 cross polarization NMR, transmission electron microscopy, X-ray photoelectron spectroscopy, and Brunauer-Emmett-Teller (BET) surface area analysis. This catalyst showed excellent catalytic activity toward the synthesis of industrially important 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF) and fructose. The process is simple, efficient, green, and industrially feasible. Oxidation of HMF proceeded in 85% yield, and dehydration of fructose followed by oxidation gave 64% yield of FDCA with 100% purity using Pd/CC catalyst and molecular O-2 as an oxidizing agent under aqueous reaction conditions. The one pot two step procedure is highly efficient for synthesis of FDCA from fructose as it avoids isolation of HMF and requires a single catalyst for two different steps. FDCA finds utility in next-generation bioplastic poly(ethylene 2,5-furandicarboxylate) (PEF), which is a replacement for fossil-fuel-based poly(ethylene terephthalate) (PET).